1977
DOI: 10.1104/pp.60.2.197
|View full text |Cite
|
Sign up to set email alerts
|

Kinetin Incorporated into Tobacco Callus Ribosomal RNA and Transfer RNA Preparations

Abstract: Kinetin, N6-furfuryladenine, was incorporated into tobacco (nicotiana tabacum L., var. Wis. No. 38) caUus RNA isolated from rapidly growing tissue cultured in the presence of N6-furfuryladenine-8-14C or unlabeled kinetin. Approximately 0.7% of the radioactivity in the labeled kinetin added to the medium was recovered as N6-furfuryladenosine (frA) in the rRNA and tRNA preparations from the tobacco cafus. The rRNA contained over 90% of these fr6A moieties. The extent of kinetin incorporation was four times great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
0

Year Published

1978
1978
1987
1987

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…Similarly, tRNA contamination could not be ruled out when weak cytokinin activity corresponding to io6A was found in tobacco callus rRNA grown in the presence of isopentenyladenine (16). Cytokinin activity has also been detected in fractionated hydrolysates of highly purified tobacco mosaic virus RNA (24).The incorporation of the cytokinins BA and kinetin into tobacco cell RNA has been found to occur preferentially into ribosomal RNA, that is, the concentration of incorporated cytokinin is three times greater in rRNA than in the corresponding tRNA (2,18,26). The physiological significance of such incorporation is not known, but these data renewed interest in the possible occurrence of endogenous cytokinins in plant rRNA.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Similarly, tRNA contamination could not be ruled out when weak cytokinin activity corresponding to io6A was found in tobacco callus rRNA grown in the presence of isopentenyladenine (16). Cytokinin activity has also been detected in fractionated hydrolysates of highly purified tobacco mosaic virus RNA (24).The incorporation of the cytokinins BA and kinetin into tobacco cell RNA has been found to occur preferentially into ribosomal RNA, that is, the concentration of incorporated cytokinin is three times greater in rRNA than in the corresponding tRNA (2,18,26). The physiological significance of such incorporation is not known, but these data renewed interest in the possible occurrence of endogenous cytokinins in plant rRNA.…”
mentioning
confidence: 89%
“…The incorporation of the cytokinins BA and kinetin into tobacco cell RNA has been found to occur preferentially into ribosomal RNA, that is, the concentration of incorporated cytokinin is three times greater in rRNA than in the corresponding tRNA (2,18,26). The physiological significance of such incorporation is not known, but these data renewed interest in the possible occurrence of endogenous cytokinins in plant rRNA.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that bzl6Ade is incorporated as the intact molecule into both the tRNA (18) and the rRNA (2), and both cytokinins have been recovered as the corresponding ribonucleosides to about three times greater extent per A2eo unit from the rRNA than from the tRNA preparations (2,14). It is not certain whether the observed incorporation of cytokinins is the result of specific events involved in the mechanism of cytokinin action or merely the result of transcriptional errors.…”
mentioning
confidence: 96%
“…
ABSTRACTThe distribution of incorporated synthetic cytokinins (N6-jS-14CIbenzyl-adenine and Evidence has been presented that the synthetic cytokinins N6-benzyladenine (bzl6Ade)3 and N6-furfuryladenine (fr6Ade, kinetin) art incorporated into RNA of cytokinin-dependent tobacco callus tissue (2,14, 18). It has been shown that bzl6Ade is incorporated as the intact molecule into both the tRNA (18) and the rRNA (2), and both cytokinins have been recovered as the corresponding ribonucleosides to about three times greater extent per A2eo unit from the rRNA than from the tRNA preparations (2, 14).
…”
mentioning
confidence: 99%
See 1 more Smart Citation